Analysis of Sandwich Plates by Generalized Differential Quadrature Method. (25th September 2013) - Ferreira, A. J. M.; Viola, E.; Tornabene, F.; Fantuzzi, N.; Zenkour, A. M.
Abstract : We combine a layer-wise formulation and a generalized differential quadrature technique for predicting the static deformations and free vibration behaviour of sandwich plates. Through numerical experiments, the capability and efficiency of this strong-form technique for static and vibration problems are demonstrated, and the numerical accuracy and convergence are thoughtfully examined.